(untitled) (Baghdad Science Journal, 2025)
In this paper we proposes the philosophy of the Darwinian selection as synthesis method called Genetic algorithm ( GA ), and include new merit function with simple form then its uses in other works for designing one of the kinds of multilayer optical filters called high reflection mirror. Here we intend to investigate solutions for many practical problems. This work appears designed high reflection mirror that have good performance with reduction the number of layers, which can enable one to controlling the errors effect of the thickness layers on the final product, where in this work we can yield such a solution in a very shorter time by controlling the length of the chromosome and optimal genetic operators . Result shows that the construction of multilayer high reflection mirror using in this approach can be considered as a master stone for design another type of filters with most complicated performance, and it is difficult designing in other approach The experiment results demonstrate that our approach is a powerful technique. It is enable to locate the global optimum optimal automatically with high confidence without need for a good starting design.